Vulnerabilities, impacts and responses to HIV/AIDS in Sub-Saharan Africa - Tadele, Getnet; Kloos, Helmut (Palgrave Macmillan, 2020)
This book examines HIV/AIDS vulnerabilities, impacts and responses in the socioeconomic and cultural context of Sub-Saharan Africa. With contributions from social scientists and public health experts, the volume identifies gender inequality and poverty as the main causes of the HIV epidemic in sub-Saharan Africa.